Wikis: 'From Each According to His Knowledge'. - O'Leary, Daniel E. (Computer (00189162), 2008)
The article reports on the use of wiki software. Wiki software allows multiple users to manipulate it by adding information quickly and easily. Ward Cunningham, in 1994, implemented the first wiki called the WikiWikiWeb on the Web site http://en.wikipedia.org/wiki/. The original software was written in the programming language Perl in the late 1980s but in 2008 wiki software applications use numerous languages such as Java, Lisp, and Smalltalk. Wikis have begun being integrated into companies where employees can keep pertinent information updated for each other's easy use.